A Multi-criteria Framework for Decision Process in Retrofit Optioneering through Interactive Data Flow. (2017) - Cecconi, Fulvio Re; Tagliabue, Lavinia C.; Maltese, Sebastiano; Zuccaro, Martina
Abstract: Aim of this research is to deliver a system of procedures and instruments that allows comparing different scenarios of restoration and retrofit of existing buildings applicable each time a relevant decision about the asset has to be made. The system developed takes advantages of Building Information Modeling (BIM) and Analytical Hierarchy Process (AHP), thus to focus on main clients' needs. Decisions about real estate assets are frequently made by managers with incomplete and scattered data, not sufficient to fully support the decision making process. Using a BIM model as a central repository of information could strongly support to compare objectively different scenarios and consequently to decide the application of a multi-criteria matrix involving management, energy, economic and social issues. BIM and BEM (Building Energy Modelling) techniques have a wide potential and analysis capabilities; however, they are often adopted without an integrated framework, causing missing performances and costs overrun. The result is a system enabling to analyze the asset, to produce BIM and BEM models ready to include life cycle data, to evaluate feasible alternatives and scenarios and to extract relevant performance indicators for decision makers' support. An existing office building in Milan representing an awkward field for intervention is the case study for the system application. While the tools and software adopted are commonly used, the system of procedures developed by the authors can be considered as an ensemble of workflows otherwise typically used independently. Using them together enhance the decision process providing data on which to set up a strategic plan of the refurbishment considering costs, continuity in occupancy and energy efficiency.